2021
DOI: 10.3390/universe7120476
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Problems for Quasinormal Modes of Black Holes

Abstract: This is an unconventional review article on spectral problems in black hole perturbation theory. Our purpose is to explain how to apply various known techniques in quantum mechanics to such spectral problems. The article includes analytical/numerical treatments, semiclassical perturbation theory, the (uniform) WKB method and useful mathematical tools: Borel summations, Padé approximants, and so forth. The article is not comprehensive, but rather looks into a few examples from various points of view. The techni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 86 publications
(175 reference statements)
1
11
0
Order By: Relevance
“…where we used r ± = M ± √ M 2 − a 2 and the numerical data of e − j and e − jk [1,2,17]. We confirmed that the Sasaki-Nakamura equation reproduces the same result in the end.…”
Section: B Second Order Expressionsupporting
confidence: 74%
See 3 more Smart Citations
“…where we used r ± = M ± √ M 2 − a 2 and the numerical data of e − j and e − jk [1,2,17]. We confirmed that the Sasaki-Nakamura equation reproduces the same result in the end.…”
Section: B Second Order Expressionsupporting
confidence: 74%
“…where we used r ± = M ± √ M 2 − a 2 and the numerical data of e − j [1,17,21]. We note that we can obtain the same result from the Sasaki-Nakamura equation if we use the recursion relation for e − j [3] (see Appendix B).…”
Section: A First Order Expressionmentioning
confidence: 68%
See 2 more Smart Citations
“…We compute slow spin corrections to the resonance frequency. To do so, we use a systematic formalism proposed in [22]. The potential (2) has a natural deformation parameter.…”
Section: Checking the Isospectralitymentioning
confidence: 99%